Ghana: Local Public Finance and Decentralization, 1994-2004 - Mogues, Tewodaj (International Food Policy Research Institute, 2012)
The purpose of this data compilation effort was to use the data for research on fiscal decentralization and public investment in Ghana. The dataset, which consists of district-level observations, covers all of Ghana’s 110 districts in existence during the period 1994 to 2004. (Since then, the number of districts in Ghana has grown as the result of administrative rearrangements.) The dataset was compiled from administrative data sources of the Ministry of Local Government, Rural Development, and Environment (MLGRDE) of Ghana, Inspectorate Division (under the then-leadership of Mr. Johnson Alifo). Some of the data were obtained directly from the Ministry, while other parts of the data had been previously obtained from the Ministry by researchers at the Institute for Statistical Social and Economic Research (ISSER) in the University of Ghana, Accra. These data are secondary, “raw” data, however were compiled and organized by IFPRI staff from both electronic sources, as well as from hardcopy sources available only in Ghanaian government physical archival records. Additional data management activities undertaken were the compilation of the data into a consistent format (e.g. each row represents a district), the application of the same spelling of districts across files, and the use of a consistent variable name across files. The values in the dataset were denoted in ‘old’ cedi, not the new Ghana cedi (GHC), which was introduced in July 2007. One new GHC is equivalent to 10,000 ‘old’ cedi. The dataset retains the denomination used in the original dataset (which pertains to the years 1994-2004, before the introduction of the GHC). The values are nominal (not adjusted for inflation). No questionnaires or other survey instruments have been used, since this was a collection of secondary administrative data. (2012-03-13)